A critical review of the effect of water storage reservoirs on organic matter decomposition in rivers - Mbaka, John Gichimu; Mwaniki, Mercy Wanjiru (NRC Research Press, 2016)
Organic matter decomposition is vital in sustaining river food webs. However, little is known about the effect of water storage reservoirs on organic matter decomposition in rivers. In this paper, we reviewed and analyzed 37 studies that investigated the effect of man-made reservoirs on organic matter decomposition in rivers. Most studies focused on decomposition of tree leaf litter (54.1%) and macrophytes litter (43.2%), while fewer studies evaluated decomposition of wood (2.7%). Based on qualitative analysis, the effect of small weirs on organic matter decomposition is local and the effect on most habitat variables is minimal. Mean effect sizes (Hedges’ g) for organic matter decomposition were −1.98 for small weirs, −1.31 for small reservoirs, and −0.66 for large reservoirs. This review demonstrates that, in general, reservoirs have a negative effect on litter decomposition. Litter decomposition, an important ecosystem process, is sensitive to impacts of reservoirs in different types of rivers.
Keywords: Dam; Organic matter decomposition; Energy source; Ecological integrity; Environment.